FACTORS CAUSED ROAD DAMAGE BANDA ACEH - MEDAN STA 481+000 - STA 483+000 - Giska Putri Wulandari; Wan Alam syah; Muhammad Zacky Ardhyan (Portal: Jurnal Teknik Sipil, 2022)
Roads are land transportation facilities that are very important in facilitating economic relations activities, both between one city and another. Good road conditions will facilitate the movement of people in relationships and other social activities. Meanwhile, if there is road damage, it will not only hinder economic and social activities, but accidents can occur. Many factors cause road damage, including weather, weather on the road surface when it rains, scorching heat in the dry season, average daily traffic volume (LHR), and vehicles that have a number of loads or overloads (Overloading). From the results of the study, the dominant type of damage on the Banda Aceh-Medan road STA 481+000-STA 483+000 sorted from the largest to the smallest percentage is Alligator Cracking, the second is Longitudinal Cracks, the third is Longitudinal Cracks. Edge (Cracked Edge).Keywords: Road, Overloading, Damage, Maintenance.